2018
DOI: 10.1007/s10803-018-3781-9
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and Interpretation of Ambiguity in Autistic Children, Typical Children and Their Mothers

Abstract: Anxiety is highly prevalent in autistic children. Yet interpretation biases implicated in anxiety in non-autistic individuals have received little research attention in this group. Twenty-two autistic children and 25 typical children completed an ambiguous scenarios interview and questionnaire-based measures of anxiety. A subsample of mothers completed parent-report and adult relevant versions of the interview and anxiety questionnaires. Autistic children self-reported similar interpretations of ambiguous scen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 92 publications
0
4
0
Order By: Relevance
“…A recent meta-analysis of all the research on the negative interpretation of ambiguity in young people with anxiety problems (Stuijfzand et al 2018 ) indicated that the effect size of this so-called interpretation bias was largest for SAD as compared to all other anxiety disorders. Finally, there is recent evidence that children with ASD who also exhibit high fear and anxiety levels in social situations display similar threat-related interpretation biases, which suggests that social anxiety is the driving force behind this type of cognitive distortion (Neil et al 2019 ).…”
Section: Commonalities and Differences In Social Difficulties Of Sm Sad And Asdmentioning
confidence: 99%
“…A recent meta-analysis of all the research on the negative interpretation of ambiguity in young people with anxiety problems (Stuijfzand et al 2018 ) indicated that the effect size of this so-called interpretation bias was largest for SAD as compared to all other anxiety disorders. Finally, there is recent evidence that children with ASD who also exhibit high fear and anxiety levels in social situations display similar threat-related interpretation biases, which suggests that social anxiety is the driving force behind this type of cognitive distortion (Neil et al 2019 ).…”
Section: Commonalities and Differences In Social Difficulties Of Sm Sad And Asdmentioning
confidence: 99%
“…This may be explained by the mixed findings both in earlier studies and in the more recent evidence (summarized in Subar & Rozenman, 2021 ). Some recent studies provided support for this link (Păsărelu et al, 2017 ; Podina et al, 2013 ) whereas others did not (Neil et al, 2019 ; Ooi et al, 2015 ). Moreover, the meta-analytic evidence for similarities in threat interpretations of parents and children must be cautiously evaluated in light of several limitations, including the relatively small number of available empirical studies, which precludes firm conclusions on this link.…”
Section: Do Parents and Children Share A Common Information Processin...mentioning
confidence: 98%
“…Definitions anxiety "Anxiety, characterized by fearful emotion, worried thoughts and physiological symptoms such as muscle tension" (Neil et al, 2019). applied behavior analysis "An application of behavioral principles to help children with ASD learn new skills (e.g., language, joint attention, play skills) and reduce disruptive behaviors" (Agazzi et al, 2017).…”
Section: Termmentioning
confidence: 99%
“…The authors could benefit from a nation-wide sample to evaluate a widespread sample. Neil et al (2019) Terms clearly defined. Researchers assigned quantitative scores to measurements that used qualitative evaluation.…”
Section: Strengthsmentioning
confidence: 99%